Ultraviolet-Irradiated All-Organic Nanocomposites with Polymer Dots for High-Temperature Capacitive Energy Storage - Ding, Jiale; Zhou, Yao; Xu, Wenhan; Yang, Fan; Zhao, Danying; Zhang, Yunhe; Jiang, Zhenhua; Wang, Qing (Nano-Micro Letters, 2023)
Polymer dielectrics capable of operating efficiently at high electric fields and elevated temperatures are urgently demanded by next-generation electronics and electrical power systems. While inorganic fillers have been extensively utilized to improved high-temperature capacitive performance of dielectric polymers, the presence of thermodynamically incompatible organic and inorganic components may lead to concern about the long-term stability and also complicate film processing. Herein, zero-dimensional polymer dots with high electron affinity are introduced into photoactive allyl-containing poly(aryl ether sulfone) to form the all-organic polymer composites for high-temperature capacitive energy storage. Upon ultraviolet irradiation, the crosslinked polymer composites with polymer dots are efficient in suppressing electrical conduction at high electric fields and elevated temperatures, which significantly reduces the high-field energy loss of the composites at 200 °C. Accordingly, the ultraviolet-irradiated composite film exhibits a discharged energy density of 4.2 J cm−3 at 200 °C. Along with outstanding cyclic stability of capacitive performance at 200 °C, this work provides a promising class of dielectric materials for robust high-performance all-organic dielectric nanocomposites. Highlights: 1 All-organic polymer composites for high-temperature capacitive energy storage. 2 Zero-dimensional polymer dots with high electron affinity are used as fillers. 3 Deep charge traps from UV-irradiated films reduce the high-field conduction loss.